2021
DOI: 10.1002/term.3255
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic fluid allograft enhances the host response to ventral hernia repair using acellular dermal matrix

Abstract: Ventral hernia repair (VHR) with acellular dermal matrix (ADM) has high rates of recurrence that may be improved with allogeneic growth factor augmentation such as amniotic fluid allograft (AFA). We hypothesized that AFA would modulate the host response to improve ADM incorporation in VHR. Lewis rats underwent chronic VHR with porcine ADM alone or with AFA augmentation. Tissue harvested at 3, 14, or 28 days was assessed for region‐specific cellularity, and a validated histomorphometric score was generated for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…In this clinical case, a combination of debridement, fluid growth factor (FGF) (which is injected as stem cells), membrane wraps, compression wraps, and skin flap reconstruction was used [10]. While most of these techniques have been implemented routinely, the literature surrounding FGF and amniotic stem cells is lacking [11]. This report serves to provide a case in which these techniques were relied upon and the patient had a successful outcome.…”
Section: Discussionmentioning
confidence: 99%
“…In this clinical case, a combination of debridement, fluid growth factor (FGF) (which is injected as stem cells), membrane wraps, compression wraps, and skin flap reconstruction was used [10]. While most of these techniques have been implemented routinely, the literature surrounding FGF and amniotic stem cells is lacking [11]. This report serves to provide a case in which these techniques were relied upon and the patient had a successful outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have highlighted the utility of AF [ 27 , 30 , 34 , 35 , 36 , 37 ] and AFC- or AEC-conditioned media [ 66 , 67 ], but the underlying mechanisms through which their therapeutic effects are mediated have received less study. Here we show that co-culturing AECs and AFCs in SFM1 produces a more diverse proteome, and that the resulting coACCM activates EMT and MFA, while AF inhibits these processes.…”
Section: Discussionmentioning
confidence: 99%
“…Cell-free AF (cfAF, herein referred to as AF for the remainder) is safe and appears to be effective in treating wounds, osteoarthritis, and other degenerative conditions in both the clinic [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ] and research lab [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. It is clear that this complex biofluid contains proteins with chemotactic, pro-growth, and anti-inflammatory properties [ 46 , 47 , 48 ], but open questions remain regarding its use in regenerative medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Zhu et al [40] indicated that ADM can provide a suitable microenvironment for adipose-derived stem cells (ADSCs), and in vivo implanted ratADSC-pADM exhibited improved vascularization and mitigated inflammatory response compared to untreated pADM. Van Eps et al [63] demonstrated that the amniotic fluid allograft treatment of ADM caused enhanced vascularization and cellularization, which was reflected by increased histomorphometric scores at 14 days.…”
Section: Effect Of Modification On Functionalitymentioning
confidence: 99%